Train Operation Plan on the Mojokerto – Wonokromo Route with Change from Single Track to Double Track on the Sepanjang Road Plot - Mulyani, Haniva; Nugroho, Agus; Tyas, Ta’tiina Nuril Ayuning (Universitas Islam Sultan Agung, 2024)
As one of the modes of transportation that is the prima donna of the community, of course the train will try to improve and provide services that are in accordance with the wishes of the community, therefore it is necessary to hold development and development in the railway. One of the double track developments on the southern route that is currently underway is the Mojokerto – Sepanjang cross, but the Sepanjang – Wonokromo route still uses a single track, causing bottlenecks. Therefore, it is important to make a double track on the Wonokromo - Sepanjang crossing so that the entire Mojokerto - Surabaya Kota cross will become a double track. The construction of this double track will affect the travel time which was originally affected due to the crossing. Likewise, changes in traffic capacity will be more than before and there will be changes in the Rail Trip Chart (GAPEKA) after the construction of the double track from the Mojokerto - Surabaya Kota route. In this study, the research method used is quantitative with secondary data collection and primary data in the form of observation by means of direct surveys at Wonokromo and Throughout stations. The results of this study were obtained, when it was double track the travel time would be shorter because there were only up and down activities for passengers and follow-ups, no more crossings. Assuming the average graphic speed using the existing speed is 73.44 km/hour. And overall travel time savings can be made of 4 hours 30 minutes (270 minutes) on the Mojokerto - Sepanjang route and the traffic capacity will increase.